Discovery, SAR, and X-ray Binding Mode Study of BCATm Inhibitors from a Novel DNA-Encoded Library - Deng, Hongfeng (ACS Med Chem Lett, 2015)
[Image: see text] As a potential target for obesity, human BCATm was screened against more than 14 billion DNA encoded compounds of distinct scaffolds followed by off-DNA synthesis and activity confirmation. As a consequence, several series of BCATm inhibitors were discovered. One representative compound (R)-3-((1-(5-bromothiophene-2-carbonyl)pyrrolidin-3-yl)oxy)-N-methyl-2′-(methylsulfonamido)-[1,1′-biphenyl]-4-carboxamide (15e) from a novel compound library synthesized via on-DNA Suzuki–Miyaura cross-coupling showed BCATm inhibitory activity with IC(50) = 2.0 μM. A protein crystal structure of 15e revealed that it binds to BCATm within the catalytic site adjacent to the PLP cofactor. The identification of this novel inhibitor series plus the establishment of a BCATm protein structure provided a good starting point for future structure-based discovery of BCATm inhibitors.